Propuesta de un manual de clasificación de puestos y un reglamento de admisión y empleo para la inmobiliaria constructora Murillo Bustamante & asociados c.a ubicada en la ciudad de Quito - Enríquez Bohórquez, Margarita Del Rosario (2014)
This research work entitled "PROPOSAL FOR A MANUAL JOB CLASSIFICATION AND REGULATION OF ADMISSION AND CONSTRUCTION JOBS FOR PROPERTIES & ASSOCIATES CA MURILLO BUSTAMANTE LOCATED IN QUITO" main objective is to develop a manual functions, allowing for efficient management in the company, to fulfill this purpose it was necessary to use deductive methods for gathering information and inductive for analysis of data obtained through research techniques such as interview and survey manager 22 employees currently working in that allowed the company to gather valuable information about the development of human talent. To carry out the project under study methods and techniques that helped make each and every one of the steps necessary for the preparation of this thesis were used. The inductive method, deductive, Analytical and Synthetic, served in the development of this research, as well as the techniques of direct observation, interview and survey staff of the company, all of this methodology allowed to analyze the functions of the company and seek alternative solutions for talent management. After research on the following relevant results: Company MURILLO BUSTAMANTE REAL ESTATE CONSTRUCTION & ASSOCIATES C.A, has been playing empirically, without giving the necessary importance to the recruitment and selection of human resources. The Job Classification Manual proposed regulate the entry of personnel as well as the assignment for each job, the same as in conjunction with the Rules of Procedure of admission and employment for human talent, clearly commit the actions and laws that apply during and after the recruitment of staff, in order to provide the company of fully trained and competent human resources for the offices. Finally, conclusions and recommendations of the paper are presented the most important being that human talent working in the company MURILLO BUSTAMANTE REAL ESTATE CONSTRUCTION & ASSOCIATES CA , Ignores the main tasks or job functions and requirements that the position, due to the lack of a description and analysis of each job, and within the recommendations we suggest considering Manual Classification of posts for the company, in order to systematically assess the performance of staff in his office, which will determine whether it meets the requirements needed for different positions.